A Conserved Mitochondrial Chaperone-Protease Complex Involved in Protein Homeostasis - Serricchio, Mauro; Bütikofer, Peter (Frontiers in Molecular Biosciences, 2021)
Mitochondria are essential organelles involved in cellular energy production. The inner mitochondrial membrane protein stomatin-like protein 2 (SLP-2) is a member of the SPFH (stomatin, prohibitin, flotilin, and HflK/C) superfamily and binds to the mitochondrial glycerophospholipid cardiolipin, forming cardiolipin-enriched membrane domains to promote the assembly and/or stabilization of protein complexes involved in oxidative phosphorylation. In addition, human SLP-2 anchors a mitochondrial processing complex required for proteolytic regulation of proteins involved in mitochondrial dynamics and quality control. We now show that deletion of the gene encoding the Trypanosoma brucei homolog TbSlp2 has no effect on respiratory protein complex stability and mitochondrial functions under normal culture conditions and is dispensable for growth of T. brucei parasites. In addition, we demonstrate that TbSlp2 binds to the metalloprotease TbYme1 and together they form a large mitochondrial protein complex. The two proteins negatively regulate each other’s expression levels by accelerating protein turnover. Furthermore, we show that TbYme1 plays a role in heat-stress resistance, as TbYme1 knock-out parasites displayed mitochondrial fragmentation and loss of viability when cultured at elevated temperatures. Unbiased interaction studies uncovered putative TbYme1 substrates, some of which were differentially affected by the absence of TbYme1. , some of which are heat-labile proteins prone to aggregate at elevated temperatures. Our results support emerging evidence for the presence of mitochondrial quality control pathways in this ancient eukaryote.